2019
DOI: 10.1037/bne0000324
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal hormone fluctuations do not affect the expression or extinction of fear-potentiated startle in female rats.

Abstract: Prior studies suggest that levels of ovarian hormones may affect learning and memory in rats, including studies of fear conditioning and extinction. We previously showed that female rats show reduced retention of extinction compared to males when measuring fear-potentiated startle, but not when measuring freezing behavior. One commonly reported observation in studies of freezing behavior is that rats with increased levels of estradiol during extinction learning show better retention of extinction than rats giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 54 publications
1
5
1
Order By: Relevance
“…Conditioning during estrous decreased spontaneous recovery in the C57Bl/6J and 129S1/SvlmJ lines but impaired extinction learning and enhanced reinstatement in the BALB/cJ line. Contrary to previous findings in rats (Blume et al, 2017; Blume et al, 2019; Bouchet et al, 2017; Chang et al, 2009; Graham and Daher, 2016; Graham and Milad, 2013; Graham and Scott, 2018; Gruene et al, 2015b; Milad et al, 2009; Rey et al, 2014; Voulo and Parsons, 2019; Zeidan et al, 2011), we did not observe enhanced extinction memory consolidation in mice undergoing the first session of extinction training in proestrus in any mouse strain. However, as we did not target behavior to specific estrous stages in these experiments, the proestrus groups in our analysis of threat conditioning dynamics stratified by cycle stage during the first extinction session are underpowered.…”
Section: Resultscontrasting
confidence: 99%
“…Conditioning during estrous decreased spontaneous recovery in the C57Bl/6J and 129S1/SvlmJ lines but impaired extinction learning and enhanced reinstatement in the BALB/cJ line. Contrary to previous findings in rats (Blume et al, 2017; Blume et al, 2019; Bouchet et al, 2017; Chang et al, 2009; Graham and Daher, 2016; Graham and Milad, 2013; Graham and Scott, 2018; Gruene et al, 2015b; Milad et al, 2009; Rey et al, 2014; Voulo and Parsons, 2019; Zeidan et al, 2011), we did not observe enhanced extinction memory consolidation in mice undergoing the first session of extinction training in proestrus in any mouse strain. However, as we did not target behavior to specific estrous stages in these experiments, the proestrus groups in our analysis of threat conditioning dynamics stratified by cycle stage during the first extinction session are underpowered.…”
Section: Resultscontrasting
confidence: 99%
“…Although the literature contains many conflicting reports on estradiol’s effects on fear- and anxiety-related behavior, our finding in LAP1 females is consistent with at least one report indicating anxiolytic effects of estrogen replacement on contextual fear behavior in rats [76]. Other studies in cycling rats have not found effects of estrous cycle on the expression of FPS [77,78,79]. These findings highlight the importance of monitoring the estrous cycle and, if possible, measuring estradiol when testing both males and females in fear-conditioning studies.…”
Section: Discussionsupporting
confidence: 90%
“…This study has some limitations, such as the use of naturally cycling females without monitoring their estrous cycle. Although previous reports showed that female hormones do not affect the expression or extinction of the FPS (Zhao et al, 2018; Voulo and Parsons, 2019), other reports showed that females fear-conditioned during proestrus show reduced FPS during the second half of fear recall test similarly to males, but females that were fear conditioned during late diestrus showed higher ASR vs. males and vs. females conditioned during proestrus, yet these findings were not replicated when measuring freezing behavior in the same study (Carvalho et al, 2021) but see (Gruene et al, 2015). A recently published meta-analysis of fear responses in female and male rodents shows that estrous cycle does not contribute to increased variability in females datasets in comparison to males (Kaluve et al, 2022).…”
Section: Discussionmentioning
confidence: 87%
“…Although FPS in humans is commonly used with varying protocols (different CS-US contingencies, predictability or order of the US) (Nelson and Shankman, 2011; Abend et al, 2022; Jovanovic et al, 2022), according to our knowledge, there are no comparative studies to date that investigated the effects of variable US predictability or contingency in rodent FPS. Furthermore, although FPS has been used in rodents, most of the studies have focused on males with a few recent exceptions (de Jongh et al, 2005; Zhao et al, 2018; Voulo and Parsons, 2019; Carvalho et al, 2021; Russo and Parsons, 2021). Considering that PTSD and anxiety-related disorders are twofold more common in women than in men (Tolin and Foa, 2006; Breslau, 2009), and higher fear reactivity to unpredictable threats is one of the hallmarks of PTSD in humans (Grillon et al, 2009), in this study we investigated how signal-threat contingency, predictability or order during fear conditioning affects FPS expression and extinction in both sexes.…”
Section: Introductionmentioning
confidence: 99%